Effect of Different Energy Levels of Microwave on Disinfection of Dental Stone Casts - Mahmood Robati Anaraki; Farzaneh Lotfipour; Elnaz Moslehifard; Ali Momtaheni; Pooyan Sigari (Tabriz University of Medical Sciences, 2013)
Background and aims. Current chemical methods may not efficiently disinfect dental stone casts. The aim of this study was to investigate if microwave irradiation is effective for disinfection of stone casts. Materials and methods. In this laboratory study, three groups (n = 162) of prepared spherical stone beads as carriers with a diameter of 10 mm were inoculated by separately soaking in three broth culture media, each containing a study microorganism-Pseudomonas aeruginosa, Staphylococcus aureus or Candida albicans. Six inoculated carriers were used for every test, including irradiation in a household microwave oven at 300, 450, 600 or 900 W energy level, or soaking in 0.03%, 0.06%, 0.12%, 0.25% or 0.50% concentration of sodium hypochlorite solution, at 1, 2, or 3-minute test times. Positive and negative control groups were considered for each test. All treated carriers were then individually transferred to nutrient broth culture medium and one milliliter from each tube was cultured in nutrient agar media over night. Colony forming unit per milliliter (CFU/mL) was counted, and multi-factor ANOVA was used to analyze data (α = 0.05). Results. Microwave irradiation at 600 W resulted in high-level disinfection in 3 minutes. Immersion of the stone casts in hypochlorite solution at 0.06% concentration resulted in disinfection after 2 minutes. Conclusion. According to the results, high level disinfection of the stone casts can be achieved by microwave irradiation at 600 W in 3 minutes, similar to a validated chemical method.